Taxonomic study of the genus Gammarus (Amphipoda, Gammaridae) from Xinjiang, China, with description of a new species - Tong, Yan; Wang, Xiaokun; Liu, Fengsong; Li, Shuqiang; Hou, Zhonge (Zootaxa, 2022)
A new species, Gammarus hoboksar Hou, sp. nov., is described from the Irtysh River basin of Xinjiang, China. The species differs morphologically from its congeners by calceoli of antenna II absent; merus and carpus of pereopods III–IV with short setae; inner ramus of uropod III about 0.79 times the length of outer ramus, terminal article of outer ramus about 0.24 times the length of first article; telson cleft, with spines and setae on surface and three spines on distal end. Phylogenetic analysis based on 28S rRNA and COI gene sequences supported the species distinctness. A key to the genus Gammarus with nine species and a map of their distributions are provided.